Bridging Endocrine Therapy for HR+/HER2- Resectable Breast Cancer: Is it Safe?. Issue 3 (March 2022) - Iles, Kathleen A.; Thornton, Madeline; Park, Jihye; Roberson, Mya; Spanheimer, Philip M.; Ollila, David W.; Gallagher, Kristalyn
Background: The COVID-19 pandemic has required new treatment paradigms to limit exposures and optimize hospital resources, including the use of neoadjuvant endocrine therapy (NAET) as bridging therapy for HR+/HER2-invasive tumors and DCIS. While this approach has been used in locally advanced disease, it is unclear how it may affect outcomes in resectable HR+/HER2- tumors. Methods: Women ≥18 years diagnosed with in situ (Tis) or non-metastatic HR+/HER2- breast cancer from March-May 2019 and 2020 were included. Fisher's exact test and two-sample t test were used to compare baseline characteristics and surgical outcomes between strata. Sub-analysis was performed between patients who received primary surgery vs a bridging NAET approach. Results: Despite similar clinical characteristics, patients in 2019 were more likely to have a surgery-first approach (75% vs 42%, P -value = .0007), receive surgery sooner (22 vs 29 days, P -value < .001), and within 60 days from diagnosis date (100% vs 85%, P -value = .0301). Neoadjuvant endocrine therapy was a more prevalent approach in 2020 (48% vs 7%, P -value < .0001). Rates of clinical to pathologic up-staging remained consistent across primary surgery vs bridging NAET subgroups ( P -value = .9253). Discussion: Pandemic-driven treatment protocols provide a unique opportunity to assess the utility of bridging endocrine therapy for resectable HR+/HER2- tumors. Differences in clinical and pathologic staging were similar across groups and did not appear to be affected by receipt of NAET. Our limited cohort demonstrates this strategic therapeutic avenue can optimize health care utilization and may be a reasonable approach when delaying surgery is preferred.